2014
DOI: 10.1155/2014/946372
|View full text |Cite
|
Sign up to set email alerts
|

The Toxic Effect of Manganese on the Acetylcholinesterase Activity in Rat Brains

Abstract: Manganese (Mn) is a naturally occurring element and an essential nutrient for humans and animals. However, exposure to high levels of Mn may cause neurotoxic effects. Accumulation of manganese damages central nervous system and causes Parkinson's disease-like syndrome called manganism. Mn neurotoxicity has been suggested to involve an imbalance between the DAergic and cholinergic systems. The pathological mechanisms associated with Mn neurotoxicity are poorly understood, but several reports have established it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Moreover, the integrity of cell membranes is influenced by the substitution of the amino group. Therefore, it was concluded that the toxic effects of the investigated particle derivatives resulted from the incorporation of aminoalkyl chains into the lipid and/or lipoprotein (Zobel et al, 1999). Similar to the current observation, Campbell et al (2005) reported that some inflammatory biomarkers such as IL1α and TNFα were increased in the lungs of mice exposed to ambient air particulate matter compared to controls.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, the integrity of cell membranes is influenced by the substitution of the amino group. Therefore, it was concluded that the toxic effects of the investigated particle derivatives resulted from the incorporation of aminoalkyl chains into the lipid and/or lipoprotein (Zobel et al, 1999). Similar to the current observation, Campbell et al (2005) reported that some inflammatory biomarkers such as IL1α and TNFα were increased in the lungs of mice exposed to ambient air particulate matter compared to controls.…”
Section: Discussionsupporting
confidence: 84%
“…This was used during the formation of polymeric nanoparticles of Valsartan-loaded Eudragit ® , Carvedilol-loaded Eudragit ® and S-nitrosoglutathioneloaded Eudragit ® for the treatment of hypertension by reducing the dose and frequency of drug administration and increasing its bioavailability (Jensen et al, 2010, Selvakumar and Yadav, 2009, Safar et al, 2015. Even though these copolymers are not biodegradable, several research groups used Eudragit ® nanoparticles (EUD-NPs) for the parenteral administration of drugs and they reported a good biocompatibility of this biomaterial (Schaffazick et al, 2008;Basarkar and Singh, 2009;Zago et al, 2013), owing to the rapid clearance from the systemic circulation by the mono-nuclear phagocytic system and their deposition in the liver (Rolland et al, 1989). However, to date, nanotechnologies raise scientific questions, including their impact on health.…”
Section: Introductionmentioning
confidence: 99%
“…Mn is elevated in dopaminergic (DAergic) neurons of the substantia nigra, providing a possible basis for the motor deficits observed in manganism 63 . Elevated Mn has been shown to affect a variety of cellular processes, including increased levels of transcription for ER-related genes 64 , ROS production 65 , mitochondrial dysfunction 66 , autophagy 67 , altered acetylcholinesterase (AChE) activity 68 , changes in cyclic AMP (cAMP) signaling 69 , iron dyshomeostatis 70 , and dysfunctional astrocytic activity 61 . Many markers of programmed cell death, including increased TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) staining, internucleosomal DNA cleavage, activation of JNK, p38, the apoptotic initiator caspase-12, and pro-apoptotic effector caspase-3, have been observed in neurons in the presence of Mn exposure 9 , 71 .…”
Section: Essential Metalsmentioning
confidence: 99%
“…Mn not only leads to manganism, which is a form of Parkinsonism, but it is also proposed to play a crucial role in PD etiology [80]. Multiple mechanisms are involved in Mn-induced neurotoxicity, including autophagy [55], oxidative stress[44], altered cAMP signaling [91], reactive oxygen species (ROS) generation [95], mitochondrial dysfunction [44], altered iron homeostasis [81] and altered acetylcholinesterase (AChE) activity [146]. Mn exposure induces α-Syn aggregation in non-human primates, and may also play a role in α-Syn protein fibrillation and oligomerization [138].…”
Section: Metalsmentioning
confidence: 99%